Weed control with saturated steam in organic highbush blueberry - Moretti, Marcelo L.; Pedroso, Rafael M. (Frontiers in Agronomy, 2023)
Weed management is a predominant and costly problem in organic blueberries. Geotextile weed fabrics of woven polyethylene, are used in organic blueberry to suppress weeds in the rows. Weeds, such as Convolvulus arvensis L., grow at the base of the blueberry plants or through openings and around the edges of the weed fabric, requiring hand weeding. This study evaluates the integration of saturated steam (SS), rotary brush (RB), and organic herbicides for weed control in blueberries. Dose-response studies indicated that SS applied at 121° C and 7.4 m 3 ha - 1 of steam (3655 MJ ha -1 ) resulted in over 90% control and reduction of dry weights of C. arvensis. When treatments were directed to the base of blueberry plants, SS at 7.4 m 3 ha -1 provided 80% control of C. arvensis 28 days after treatment (DAT) and was comparable to hand-weeding. Both of these treatments outperformed capric plus caprylic acid (CC) (33.2 kg ai ha -1 ) or ammonium nonanoate (AN) (24.3 kg ai ha -1 ) applications despite C. arversis regrowth being observed. Four repetitive basal applications of SS of up to 29.6 m 3 ha -1 over two consecutive years caused minimal and transient damage to new basal shoots of 'Elliot' and 'Duke' blueberries; basal shoot crosssectional area compared to nontreated was unaffected. In contrast, basal application of AN treatments damaged or killed basal shoots. When treatments were applied to the edge of the weed fabric, SS (7.4 m 3 ha -1 ) reduced weed biomass by 42 to 93% at 28 DAT compared to nontreated. RB reduced weed biomass from 72 to 99% in all experiments, while CC and AN reduced biomass by 18 to 54%. A partial budget analysis indicated SS and RB were 3- and 6.5-fold less expensive than organic herbicides. Integrating physical (SS) and mechanical (RB) means improved weed control. The latter, however, damaged the weed fabric where preexisting holes were present, generated dust, and increased the chance of fruit contamination. SS was safe for the weed fabric and blueberry, but weed regrowth and copious water requirements hindered its feasibility.